Determination of bacterial endotoxins for the kinetic chromogenic method in the injectable Cefepime - Medina Borges, Raisa Inés (2019)
In the present work the Lal method in it kinetic chromogenic variant for the determination of bacterial endotoxins in the injectable Cefepime 1 g is evaluated. The objective of this variant consists in the control of the color development through the time and it uses a standard curve represented by the reaction time as function of the known concentration of endotoxins. The characterization of the product was carried out. The selection of the dilution of work was preliminarily evaluated in the inhibition and rehearsal assay. The elected dilution was validated in three serial lots of the product and it was observed, in all the cases, recovered percent framed inside the established limits. It was demonstrated that the standardization and validation of the method allowits application as routine assay for the determination of bacterial endotoxins as a part of the quality control for this product